The Triumph of the blue in nature and in Anthropocene. (February 2023) - Pina, Fernando; Basílio, Nuno; Parola, A.J.; Melo, Maria J.; Oliveira, Joana; de Freitas, Victor
Abstract: Blue was the last color to be spread in Nature by the anthocyanins present in angiosperms, and the last color to be managed by Humans in Anthropocene. Blue also appears in a small number of algae, fungi, and bacteria, but these living beings have very little to do with the profusion of a natural blue hue. Humanity took many long years to figure out how to reproduce and use blue - the classic example of which is indigo dye, extracted from plants like the Indigofera tinctoria . However, even simple anthocyanins are not capable of achieving blue. Plants had to develop strategies to fix this color, mainly by intramolecular copigmentation in acylated anthocyanins and complexation with metals, as in metalloanthocyanins. Blue was absent in the first paleolithic cave paintings. Those depictions were made using reds, yellows, and blacks of all hues, but no blue. In addition, blue LEDs and LASERs came later after red and green. It was only at the end of the 20th century that genetic engineering was able to create blue flowers adapted to the markets to meet consumer demands. Food and beverage producers continue to look for a natural blue as an alternative to synthetic colorants. Blue remained a second-rate color in the West for a long time. Despite that fact, in many countries blue is now the preferred color. In this review we track the appearance of blue in Nature and in the Anthropocene. Graphical abstract: Image 1 Highlights: Simple anthocyanins are unable to confer blue color. While ubiquitous the blue was a color that the human beings reproduced, made and mastered difficultly and tardily. Blue is the last color to be diffused in Nature and in many applications and discoveries by Humans in Anthropocene.